Virtual Reality Mindfulness for Meta-Competence Training among People with Different Mental Disorders: A Systematic Review - Eleni Mitsea; Athanasios Drigas; Charalabos Skianis (Psychiatry International, 2023)
International psychiatry is facing major challenges due to the rapid increase in mental health issues. The forthcoming mental health crisis has opened the debate about the need to broaden the therapeutic horizons with the implementation of digitally assisted mindfulness practices within psychotherapeutic interventions. Mindfulness training is developing into a promising intervention for a variety of health problems and a booster of well-being. At the same time, virtual reality (VR) and especially immersive technologies are increasingly being used as assistive tools in the training of people with special education needs and disabilities (SEND). Μeta-competences refer to a set of self-development skills that incorporate meta-cognitive and meta-emotional attributes, enabling individuals to be self-conscious, self-regulated, and flexible in every aspect of human life. The current review aims to investigate (i) the efficacy of mindfulness strategies in meta-competence training for SEND and (ii) the role of VR as an assistive technology in mindfulness training. The PRISMA 2020 methodology was utilized to respond to the objectives and research questions. The database search provided 1380 records, and 29 studies met the inclusion criteria. The results showed that mindfulness training has the potential to train meta-cognitive and meta-emotional competences among people with different mental disorders, including Attention Deficit/Hyperactivity Disorder (ADHD), Autism Spectrum Disorder (ASD), Intellectual Disability (ID), Depressive Disorder, Stress Disorder, and Specific Learning Disorder. VR was found to be an effective assistive technology, providing significant advantages compared to conventional mindfulness interventions. Mindfulness training assisted by immersive technologies was found to significantly improve a wide range of cognitive and socio-emotional meta-competences, including self-awareness, inhibition control, attention regulation, flexibility, positive thinking, and emotional regulation. The results of this systematic review may provide positive feedback for creating inclusive digital training environments.